Effectiveness of Kinesio Taping and Retro Walking Exercise on the Knee Range of Motion in Older People with Osteoarthritis - Yulian Pristanti Sani Putri; Atika Yulianti (Physical Therapy Journal of Indonesia, 2020)
Background: Osteoarthritis (OA) is a degenerative disease of the synovial joint marked by chondropathy with the proliferation of new bone and also renovation of joint contour. Knee OA is associated with age, gender, and excessive weight conditions, conservatively treated using physical therapy intervention such as Kinesio taping and retro walking exercise to enhance the range of motion of knee joint. This study aimed to compare the effectiveness of Kinesio taping and retro walking exercise on the knee range of motion in older people with osteoarthritis. Methods: This study used quasi-experimental two groups pre-test and post-test design, which was involving 30 respondents by using purposive sampling as a sample collection technique. Additionally, the sample was divided into two intervention groups. Furthermore, the obtained data were analyzed using the Mann Whitney test. Results: After the intervention period, pre-test and post-test within-group analysis showed a significant improvement of knee ROM in the Kinesio taping group (P<0.001) and retro walking group (P=0.019). Furthermore, the analysis for mean differences of pre-test and post-test between-group comparison accepted the study hypothesis that Kinesio taping had a bigger effect than retro walking exercise to improve knee ROM (P=0.01). Conclusion: Both Kinesio taping and retro walking exercises were influencing ROM improvement in the elderly. However, the mean result showed that Kinesio taping was giving more influence in enhancing ROM as compared to retro walking exercise.